Unwanted traffic in 3G networks. - Ricciato, Fabio
The presence of "unwanted" (or background) traffic in the Internet is a well-known fact. In principle any network that has been engineered without taking its presence into account might experience troubles during periods of massive exposure to unwanted traffic, e.g. during large-scale infections. A concrete example was provided by the spreading of Code-Red-II in 2001, which caused several routers crashes worldwide. Similar events might take place in 3G networks as well, with further potential complications arising from their high functional complexity and the scarcity of radio resources. For example, under certain hypothetical network con guration settings unwanted traffic, and specifically scanning traffic from infected Mobile Stations, can cause large-scale wastage of logical resources, and in extreme cases even starvation. Unwanted traffic is present nowdays also in GPRS/UMTS, mainly due to the widespread use of 3G connect cards for laptops. We urge the research community and network operators to consider the issue of 3G robustness to unwanted traffic as a prominent research area.
Keywords: Computer systems organization; Computer communication networks; Network operations; Public networks; Network monitoring; Measurement; Reliability; Security